Interactions of GFAP with ceftriaxone and phenytoin: SRCD and molecular docking and dynamic simulation - Ruzza, Paolo; Vitale, Rosa Maria; Hussain, Rohanah; Biondi, Barbara; Amodeo, Pietro; Sechi, GianPietro; Siligardi, Giuliano (Biochimica et biophysica acta, 2016)
GFAP is the major intermediate filament protein in mature astrocytes. Its increased expression and aggregation was firstly associated to Alexander's disease, and successively in different neurological diseases including scrapie, Alzheimer's and Creutzfeld–Jacob diseases. Recently, ceftriaxone a multi-potent β-lactam antibiotic able to overcome the blood–brain barrier, successfully eliminated the cellular toxic effects of misfolded mutated GFAP, similarly to phenytoin sodium, in a cellular model of Alexander's disease and inhibited α-synuclein aggregation protecting PC12 cells from the exposure to 6-hydroxydopamine. In this study, synchrotron radiation circular dichroism spectroscopy has been used to obtain structural information about the GFAP-ceftriaxone (phenytoin) interactions, while computational methods allowed the identification of the relevant putative binding site of either ceftriaxone or phenytoin on the dimer structure of GFAP, permitting to rationalize the spectroscopic experimental results. We found that GFAP exhibited enhanced stability upon the addition of two equivalents of each ligands with ceftriaxone imparting a more spontaneous interactions and a more ordered complex system than phenytoin. SRCD data and MD models indicate a stronger protective effect of ceftriaxone in neurological disorders characterized by an increased production and polymerization of GFAP. This result, in addition to our previous works in which we documented that ceftriaxone interacts with α-synuclein inhibiting its pathological aggregation and that a cyclical treatment with this molecule in a patient with adult-onset Alexander's disease halted, and partly reversed, the progression of neurodegeneration, suggests the possibility of a chaperone-like effect of ceftriaxone on protein involved in specific neurodegenerative diseases. [Display omitted] •Hints on therapeutic mechanism of ceftriaxone and phenytoin in GFAP related pathologies•Insights into ceftriaxone and phenytoin effects on GFAP from docking and molecular dynamics•Validation of ceftriaxone and phenytoin interaction with GFAP by SRCD UV-photo denaturation assay